Penanaman Nilai-Nilai Kewirausahaan Prespektif Islam - Muyassaroh, Laili Yatul; Farwati, Sizka (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2023)
In the Islamic view, entrepreneurship is considered as a form of worship that can improve the economy of Muslims and society in general. This is because the effort to seek sustenance is regarded as an act that is desired by Allah SWT. This study discusses the concept and value of entrepreneurship in Islam with the research method used is library research or library research with the type of document / text study research. The results showed that one of the factors that supports human self-development in various business / business activities is the application of religious elements and values. In order for business / business to run in accordance with Islamic teachings, humans need to activate their potential for Islamic spiritual intelligence in realizing these religious elements and values. Islamic teachings place the position of human efforts in meeting their needs can be valued as worship if done with the intention of Allah. The creative and innovative process can only be done by people who have an entrepreneurial attitude. The concept of entrepreneurship in Islam includes attitudes of trustworthiness, goodness, friendly service, and done solely for worship. The values ​​of entrepreneurship in Islam also include self-confidence, initiative, achievement, forward-looking, having leadership skills, and taking risks. This study provides an important contribution in enriching the understanding of entrepreneurship in the Islamic perspective and can be a reference for Muslim entrepreneurs in running their businesses.